Theoretical perspectives of integrating technology into English language learning - Mali, Yustinus Calvin Gai (Universitas Lancang Kuning, 2024)
Three issues of technology integration into English language learning are present: inquiries on what and how technology is used to support language learning, ignorance of theoretical foundations and technology standards as a basis to design technology-supported language tasks and instructions, and English language teachers’ attitudes that put technology far ahead of language learning. In response to these issues, this theoretical paper aims to discuss resources where teachers can find reliable technology to support their language teaching practices. It continues to explain language learning and task engagement principles and technology standards as a basis for designing language tasks and instructions. The author supports the discussions with relevant literature and instances of some technology-supported language tasks. The paper then proposes a professional learning community meeting where the teachers can learn collaboratively with their colleagues in a supportive learning environment on how to use various tech applications. The paper concludes that teachers with principled ways of using technology should perform better in supporting students’ learning with technology than those who design a technology-based task and instruction mainly based on their personal (and biased) experiences on what worked well with technology.